Dynamics of Fiscal Policy in Islamic Countries and Muslim Countries: Pakistan, Saudi Arabia, and Indonesia - Muhammad Asro; Sofyan Al Hakim; Iwan Setiawan (Ihtifaz: Journal of Islamic Economics, Finance, and Banking, 2023)
Introduction: This research departs from the discussion of Islamic fiscal policy in Islamic countries and Muslim countries, where the dynamics of fiscal policy in Islamic countries and Muslim countries with various strategies to achieve the ideal fiscal. But to achieve the ideal of fiscal policy, there are challenges and obstacles that are not simple, because fiscal with all its dynamics must be carried out seriously for any country. Both Islamic countries, Muslims, and even other countries in general. Purpose: This study aims to determine the dynamics of fiscal policy in Islamic countries and Muslim countries, especially in Pakistan, Saudi Arabia, and Indonesia. Methodology: This research uses a descriptive qualitative method with a juridical research approach, which is an approach using the provisions of laws and regulations that apply to a country or a doctrinal legal approach method, namely legal theories, and opinions of legal scientists, especially with the problems discussed. Findings: The results of this study can be concluded as follows: First, fiscal policy in Islamic countries and Muslim countries continues to experience developmental dynamics. In addition, the development strategies implemented are often less comprehensive and pay less attention to the strengths possessed by the country in question. So, it often faces difficulties that are not light in building superiority and competitiveness; Second, the dynamics of fiscal policy differences as mentioned above prove that they are still in a state of facing an economic crisis, but countries in the Middle East, North Africa, and Central Asia, vary in their fiscal policy determination. Regarding fiscal policy in some Islamic countries, some countries formally apply zakat collection laws in their economic policies, such as Saudi Arabia, Libya, Jordan, Bahrain, Pakistan, Kuwait, Yemen, Sudan, and Indonesia.